رؤى النخبة الدينية للقضايا السكانية بين الاعتقاد والفاعلية: دراسة سوسيو ديموجرافية - حجازي، هاني محمد بهاء الدين علي; مهني، جلال محمد نجيب محمد (جامعة عين شمس - مركز بحوث الشرق الأوسط, 2024)
استهدفت الدراسة بحث القضايا السكانية في رؤى النخبة الدينية بين الاعتقاد والفاعلية، والتركيز على الإشكالي والجدلي منها كقضايا (الزواج المبكر للفتيات، وختان الإناث، والفحص الطبي ما قبل الزواج)، وذلك في إطار من العلاقة الارتباطية بين قضايا السكان وخصائصهم النوعية، وتحقيق أهداف التنمية المستدامة. واعتمدت الدراسة في بحثها على المنهج العلمي بأسلوبه التحليلي الكيفي، عبر تركيب منهجي يتوسل تقنيتين (الاستنباط والاستقراء) مع ترجيح الأخير، باعتباره تصورا ورؤية للوقائع والحقائق الموجودة في حياتنا اليومية. هذا إلى جانب المقارنة الجزئية لرؤى النخب الدينية موقفيا من القضايا السكانية موضوع الدراسة، عن طريق (المقابلة المتعمقة)، وفقا لآلية (التصعيد) تبدأ بالأسئلة التي ترتبط بخصائص النخبة الدينية لتنتهي تدريجيا بالأسئلة التي ترتبط بخصائص القضية السكانية، وعليه تم تصميم دليل للمقابلة يفي بهذا الغرض. وبالتطبيق على عينة من النخب الدينية (المسلمة، والمسيحية) بمحافظة السويس، بلغت (34) حالة، عن طريق المعاينة الغرضية غير الاحتمالية. وتم تحليل البيانات المتحصلة ميدانيا وفق مقترح نموذج تحليلي للقضايا السكانية في رؤى النخبة الدينية، وفق مستويين من مستويات التحليل الكيفي (الأفقي والرأسي)، وتم تفسير نتائجها المتحصلة عبر برادايم ونموذج تفسيري مقترح لفهم قضايا الدراسة ومقاربتها سوسيولوجيا. وجاءت نتائج الدراسة مؤكدة أن تداخلات المعتقد والموروث الثقافي، والعوامل الدينية والمتصلة بالفهم الخاطئ للنصوص الدينية المقدسة المتعلقة ببعض القضايا السكانية عند العامة، وبعض من النخبة الدينية لا يزال يسهم في الدفع ببعض القضايا السكانية نحو مزيد من الاستمرار والممارسة الاجتماعية، وأن رؤى النخبة الدينية باختلاف خصائصها الاجتماعية ذات معرفة واعية بالقضايا السكانية، أكدت عليها من خلال إبراز مفهومها، وتقدير حجمها مجتمعيا، استشهادا بملاحظات ونماذج واقعية، وتباينت رؤاهم ومواقفهم من تلك القضايا بصورة جدلية بين الرفض والقبول المطلق، والقبول والرفض المشروط، ودلالات ذلك وأثره على القضايا واستمراريتها أو انحسارها، وجاء الأثر الصحي والسوسيو ديموجرافي في مقدمة الآثار المترتبة على هذه القضايا، وفي إطار من التشبيك بين الدوافع والأسباب المسببة لتلك القضايا جاءت الأسباب السوسيو ثقافية في صدارتها لا سيما تداخلات المعتقد والموروث الثقافي، وتباينت رؤى النخبة إزاء المسئولية الاجتماعية للمجتمع بحسب موقفهم العام من كل قضية. وجاءت ميكانيزمات المعالجة السوسيولوجية لجميع القضايا مرتكزة على الجانب (الوقائي) فقط مع إشارات هامشية لكل من الجانب (العلاجي والإنمائي). وتؤكد جميع القضايا في نهايتها ضرورة معالجة الأعراف الاجتماعية والسلوكيات التي يتم الحفاظ عليها من خلال توقعات المجتمع والمعتقدات البالية، وتأكيد دور النخبة الدينية في الحد من استمرار الممارسات المناهضة للقضية السكانية. The study aims to explore population issues through the perspectives of the religious elite, focusing on the interplay between belief and effectiveness. It emphasizes contentious and debatable issues such as early marriage of girls, female genital mutilation (FGM), and premarital medical examinations. This is examined within the context of the relationship between population issues and their qualitative characteristics, in line with achieving sustainable development goals. The study employs a qualitative analytical scientific method, utilizing both deductive and inductive techniques, favoring the latter as it reflects a vision and understanding of everyday realities. Additionally, the study involves a partial comparison of the stances of the religious elite on population issues, using in-depth interviews. These interviews start with questions related to the characteristics of the religious elite and gradually move to questions related to the characteristics of the population issues, thus a structured interview guide was designed for this purpose. The study was applied to a sample of religious elites (both Muslim and Christian) in the Suez Governorate, comprising 34 cases selected through purposive non-probability sampling. The field data were analyzed using a proposed analytical model for population issues through the perspectives of the religious elite, employing both horizontal and vertical qualitative analysis levels. The results were interpreted through a proposed paradigm and interpretive model to The findings understand and sociologically approach the study issues. of the study indicate that the interactions between belief, cultural heritage, religious factors, and the misinterpretation of sacred religious texts concerning certain population issues among the general public and some religious elites continue to perpetuate these issues socially. The religious elite, despite their differing social characteristics, demonstrated a conscious awareness of population issues by highlighting their concepts and assessing their societal significance, using real-life observations and examples. Their perspectives and stances on these issues varied significantly, ranging from absolute acceptance or rejection to conditional acceptance or rejection. These perspectives and their implications affect the persistence or decline of these issues, with health and socio-demographic impacts being the most prominent consequences. The study identifies socio-cultural reasons, particularly the interactions between belief and cultural heritage, as primary drivers of these issues. The religious elite's views on societal responsibility varied according to their overall stance on each issue. Sociological treatment mechanisms for all issues focused primarily on the preventive aspect, with marginal references to both therapeutic and developmental aspects. Ultimately, the study underscores the necessity of addressing social norms and behaviors upheld by societal expectations and outdated beliefs, highlighting the role of the religious elite in curbing practices that oppose population issue resolutions.
Keywords: المجتمع المصري -- القضايا السكانية -- قضية ختان الإناث -- زواج الأطفال